If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3z+2/9=4z+1/9
We move all terms to the left:
3z+2/9-(4z+1/9)=0
We add all the numbers together, and all the variables
3z-(+4z+1/9)+2/9=0
We get rid of parentheses
3z-4z-1/9+2/9=0
We multiply all the terms by the denominator
3z*9-4z*9-1+2=0
We add all the numbers together, and all the variables
3z*9-4z*9+1=0
Wy multiply elements
27z-36z+1=0
We add all the numbers together, and all the variables
-9z+1=0
We move all terms containing z to the left, all other terms to the right
-9z=-1
z=-1/-9
z=1/9
| (7x)+40=20 | | (7x)+40=22 | | 4(-6n-4)=128 | | 2/9(3x-1/2)=1/5x+1/3 | | r^-16=-7 | | -10=-5x-25*4 | | x/14+30=70 | | 16p+1=-31 | | 2(s+11)=5(s+2)* | | 2/5x-81/8-3/4(14/15x-55/9)=27/10x-25/6+3/4(x+51/6) | | 8(g-3)=24* | | 16p+1=−31 | | 6(x-2)/9=2(x+3)/8 | | x2-3x=2x+36 | | y=821(1-0.15)^0.5 | | y=821(1+0.15)^0.5 | | x2-3×=2×+36 | | y=100(1-0.22)^5 | | 8s+82=90 | | s/s+12=17 | | 8-(-12x)=-14 | | 2x-3/4=-3 | | -15+20x=20x-15 | | 8x-(-12)=-14 | | Y/y-6=4 | | 82=-7(3r-8)+5 | | -5x=-71/7 | | 5x+3x+9=x | | -5/3=14/3x | | X3*x=5 | | y=100(1+0.22)^5 | | r^-17=-7 |